2012
DOI: 10.1371/journal.pmed.1001336
|View full text |Cite
|
Sign up to set email alerts
|

The Brazil SimSmoke Policy Simulation Model: The Effect of Strong Tobacco Control Policies on Smoking Prevalence and Smoking-Attributable Deaths in a Middle Income Nation

Abstract: David Levy and colleagues use the SimSmoke model to estimate the effect of Brazil's recent stronger tobacco control policies on smoking prevalence and associated premature mortality, and the effect that additional policies may have.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
179
0
32

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(219 citation statements)
references
References 30 publications
8
179
0
32
Order By: Relevance
“…Tobacco represents a risk factor for different pathologies though, resulting in the implementation of public policies such as damage reduction. (25) These study results were similar to a study developed in Sulaymaniyah, Iraq, involving health professionals who worked at teaching hospitals. Tobacco consumption was present in 26.5% of the subjects and predominant among workers with longer time working at the institution, which corresponded to the older individuals.…”
Section: Discussionsupporting
confidence: 84%
“…Tobacco represents a risk factor for different pathologies though, resulting in the implementation of public policies such as damage reduction. (25) These study results were similar to a study developed in Sulaymaniyah, Iraq, involving health professionals who worked at teaching hospitals. Tobacco consumption was present in 26.5% of the subjects and predominant among workers with longer time working at the institution, which corresponded to the older individuals.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the relatively high price of cigarettes in Brazil, considered the highest in the world, may also have contributed to this reduction 30 . Our results are corroborated by the findings of studies in high income countries that observed a higher rate of current smoking prevalence among patients with mental illnesses than in the general population 5,6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Results from a national survey indicate that in 2008 prevalence was 18.5%, showing a significant reduction when compared with the 1989 data 10 . Advances in tobacco control in Brazil seen over the last decades are positive, but it is observed that prevalence among young women is growing more than among men of the same age 11 , mortality is still high 12,13 and the costs are underestimated 14 . In this scenario, calculation of the tobacco-related disease burden is not often made in the country.…”
Section: Introductionmentioning
confidence: 99%